2021
DOI: 10.3390/ijms22030992
|View full text |Cite
|
Sign up to set email alerts
|

Can SARS-CoV-2 Virus Use Multiple Receptors to Enter Host Cells?

Abstract: The occurrence of the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), responsible for coronavirus disease 2019 (COVD-19), represents a catastrophic threat to global health. Protruding from the viral surface is a densely glycosylated spike (S) protein, which engages angiotensin-converting enzyme 2 (ACE2) to mediate host cell entry. However, studies have reported viral susceptibility in intra- and extrapulmonary immune and non-immune cells lacking ACE2, suggesting that the S protein may explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 269 publications
(476 reference statements)
1
119
0
2
Order By: Relevance
“…This suggests that the elevated CXCL9 and CXL10 in MIS-C are probably markers of increased IFN-g production in lymphoid organs and of secondary induction of pro-inflammatory cytokines and chemokines (e.g., IL-6, CXCL8, CCL2) by macrophages. In addition, the increase of these chemokines in patients with MIS-C might be partially related to the interaction of PAMPs and viral molecules with innate immune receptors, such as TLR3 (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the elevated CXCL9 and CXL10 in MIS-C are probably markers of increased IFN-g production in lymphoid organs and of secondary induction of pro-inflammatory cytokines and chemokines (e.g., IL-6, CXCL8, CCL2) by macrophages. In addition, the increase of these chemokines in patients with MIS-C might be partially related to the interaction of PAMPs and viral molecules with innate immune receptors, such as TLR3 (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The oral epithelial cells including the taste bud cells have been shown to express angiotensin-receptor-2 (ACE2), the entry receptor for viruses of the Coronaviridae family including the SARS-COV-2. Emerging evidence also suggest that the CoV-2 potentially uses multiple entry receptors such as the sialic acid receptors and the toll like receptors (TLR) for host cell entry (Vaira et al, 2020;Gadanec et al, 2021). Binding of SARS-CoV-2 to salivary sialic acid could interfere with the glycoproteins mediated transport of tastants and contribute to loss of taste (Milanetti et al, 2021).…”
Section: Pathogenesis Of Taste Dysfunction In Long Covid-19mentioning
confidence: 99%
“…A cryo-electron microscopy study has already suggested that coronaviruses mask important immunogenic sites on their surface by glycosylation 46 . Furthermore, recent work suggests that changes in glycosylation sites on the S protein of the virus may affect recognition of the S protein by other potential human proteins and receptors, inducing the toll-like receptors, calcitonin-like receptors, and heat shock protein GRP78, thus leading to a more severe inflammation that characterizes a more severe form of COVID-19 47 .…”
Section: Discussionmentioning
confidence: 99%